PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT HABIBI MAULANA TEKNIK DI CIKARANG - Rizki Habib Maulana; Haidilia Maharani (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the effect of Reward and Punishment on Employee Performance both partially and simultaneously at PT Habibi Maulana Teknik in Cikarang. This research method uses quantitative methods with a descriptive approach. The data collection methods used are primary data and secondary data. The sampling technique in this research used the saturated sample, namely 60 respondents. Data analysis used the SPSS version 29 program. The analysis techniques used were validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, auto correlation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test and hypothesis test. Partially testing the hypothesis for the Reward variable (X1) obtained a value of tcount > ttable (2.253 > 1.671) and a significance value of 0.028 < 0.05. This means that Reward (X1) has a significant effect on Employee Performance (Y). Partially testing the hypothesis for the Punishment variable (X2) obtained a value of tcount > ttable (1.927 > 1.671) and a significance value of 0.059 < 0.05. This means that punishment (X2) has a significant effect on employee performance (Y). Simultaneous hypothesis testing obtained a value of fcount > ftable (10.593 > 3.162) and a significance value of 0.000 < 0.05. So it can be concluded that Reward (X1) and Punishment (X2) simultaneously have a significant effect on Employee Performance (Y). The determination obtained by R Square is 0.271, meaning that the Reward and Punishment variables together have an influence contribution of 27.1% on employee performance. Meanwhile, the remaining 72.9% was influenced by other factors not examined in this study.